The Study of Baffles Effect on Temperature in Shell and Tube Heat Exchanger - Abd Razak, Siti Nur Hidayah; Sapit, Azwan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Heat exchangers find wide usage in a variety of industry applications. It is a device that works by facilitating the transfer of thermal energy between two fluids at different temperatures with circulate through separate pathways to avoid direct contact. Shell and tube is one of the most common type of heat exchanger used in the industry. The basic design consists of a series of tubes enclosed within a cylindrical shell. Baffles are placed in the shell side to create turbulence in the shell-side fluid, which improves heat transfer efficiency. This study investigates how the presence or absence of baffles affects heat transfer rates within the exchanger, exploring the intricate dynamics of fluid flow and heat exchange. SolidWorks 2023 software has been utilized to design and simulation analysis of the shell and tube heat exchanger. The goal of this study is to measure the impact of baffles on heat transfer rates, fluid dynamics, and total energy efficiency through analysis of computational fluid dynamic (CFD) simulation. The result of this study are expected to enhance the efficiency and effectiveness of shell and tube heat exchanger.